2003
DOI: 10.1128/jvi.77.13.7254-7260.2003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Rotaviruses with Hsc70 during Cell Entry Is Mediated by VP5

Abstract: Rotavirus infection seems to be a multistep process in which the viruses are required to interact with several cell surface molecules to enter the cell. The virus spike protein VP4, which is cleaved by trypsin into two subunits, VP5 and VP8, is involved in some of these interactions. We have previously shown that the neuraminidase-sensitive rotavirus strain RRV initially attaches to a sialic acid-containing cell molecule through the VP8 subunit of VP4 and subsequently interacts with integrin ␣2␤1 through VP5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
92
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 30 publications
4
92
0
3
Order By: Relevance
“…We have previously established that rotavirus particles interact with hsc70 through a region near the carboxy-terminal region of VP5 (45). To determine whether the interaction of TLPs with the PB domain of hsc70 was through the same region of VP5, the amino-terminal portion of VP5 (VP5-248; residues 274 to 474) or the carboxy-terminal part of this protein (VP5-474; amino acids 474 to 776) was expressed in bacteria and purified by affinity chromatography (45).…”
Section: Results Hsc70 Binds To Rotavirus Through Its Peptide-bindingmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously established that rotavirus particles interact with hsc70 through a region near the carboxy-terminal region of VP5 (45). To determine whether the interaction of TLPs with the PB domain of hsc70 was through the same region of VP5, the amino-terminal portion of VP5 (VP5-248; residues 274 to 474) or the carboxy-terminal part of this protein (VP5-474; amino acids 474 to 776) was expressed in bacteria and purified by affinity chromatography (45).…”
Section: Results Hsc70 Binds To Rotavirus Through Its Peptide-bindingmentioning
confidence: 99%
“…To determine whether the interaction of TLPs with the PB domain of hsc70 was through the same region of VP5, the amino-terminal portion of VP5 (VP5-248; residues 274 to 474) or the carboxy-terminal part of this protein (VP5-474; amino acids 474 to 776) was expressed in bacteria and purified by affinity chromatography (45). These recombinant polypeptides were preincubated with either the complete hsc70 protein or its PB domain, and these mixtures were then added to ELISA plates coated with TLPs.…”
Section: Results Hsc70 Binds To Rotavirus Through Its Peptide-bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…Other heat shock proteins have already been shown to be involved in rotavirus infection. The 70-kDa heat shock cognate protein (Hsc70), whose level is not modified upon rotavirus infection, has been shown to play a role in the entry process of the virus (15,41) thanks to its well-known involvement in the clathrin-coated vesicle formation process (18). Previous works have shown that the levels of other members of the Hsp superfamily, namely, Grp78 and Grp94, also increased upon rotavirus infection of MA104 cells (8,39), but the exact function of this phenomenon has not been documented further.…”
Section: Discussionmentioning
confidence: 99%